Congenital bilateral anterior nasal atresia in 16 half‐sibling Holstein‐Friesian calves. Issue 4 (April 2017) - McGowan, M; Smith, C; Ferguson, A; Stone, B; Vankan, D; Allavena, R
Abstract : Case report: Cases of bilateral anterior nasal atresia, sometimes referred to as arhinia or partial arhinia, are extremely rare in cattle and have only been reported as single events. This report describes the birth of 16 Holstein Friesian calves over a 3‐month period, all affected with bilateral atresia of the nares and anterior nasal cavity, with 2 calves having additional severe deviation of the nasomaxillary bones and nasal septum. One affected calf was born with an anatomically normal twin. Parentage testing demonstrated that a single Holstein Friesian bull sired all cases tested. Conclusion: This is the first report of multiple cases of bilateral anterior nasal atresia in cattle with evidence that demonstrates a heritable condition.